Semiotic Analysis of Selected Sign Interpretation in Public Space Using Saussure’s Theory - Ridwan, Ahmad Faisal; Giblatar, Alfarazhi; Radityo, Radityo; Oktavia, Indah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study explores the semiotics of public signs using Ferdinand de Saussure's theory, focusing on the relationship between signifiers (visual and verbal elements) and their signified meanings. Employing a qualitative descriptive method, the research analyzes 15 visual signs, such as traffic indicators, warning symbols, and informational signage, alongside 9 verbal signs, including textual instructions and prohibitions, observed in urban environments. The findings reveal that visual signs, including colors, symbols, and imagery, effectively convey universal messages, while verbal signs enhance clarity and context, making communication accessible to diverse audiences. Together, these components ensure the messages are accessible to diverse audiences, enhancing communication, safety, and inclusivity in public spaces.